Social Media Marketing Activities' Impact On Brand Image, Brand Loyalty, And Awareness - Zainul Wasik; Niken Savitri Primasari; Didik Setiawan (Journal of Managerial Sciences and Studies, 2025)
The purpose of this study is to look into how social media marketing campaigns affect brand awareness, brand loyalty, and brand image.. Analysing the relationship between brand awareness and brand image and brand loyalty is another goal of this study. The group under study consists of customers who actively follow the five businesses with the highest social ratings on Facebook, Twitter, Instagram, and other social media sites.. Convenience sampling was used in this study to gather information from 600 brand fans using online questionnaires shared on social media. This analysis also made use of quantitative methods. The gathered data has been examined using structural equation modelling (SEM). While using social media for marketing initiatives enhanced brand loyalty and image overall, the study discovered that brand awareness had the most noticeable impact. Furthermore, research indicates that brand loyalty is significantly influenced by brand cognition and image. Furthermore, a weak association between brand awareness and brand image has been shown by this study.